A Development Framework for Social Media Interaction in Learning Management System - Ravisekaran, Kalaivani; Ramakrishnan, Sivakumar (International Journal of Engineering and Technology, 2018)
Learning Management System (LMS) plays a vital role and an imprortant part in technology-enhanced learning. It presents different services to enhance the education procedure in ubiquitous learning condition. But, it is found that in existing education MS a extend range of education procedure and process are presented. But, it needs to be developed with some ubiquitous additional functionality. So the current research we proposed a struture for LMS to integrate social media services to make the LMS enrich in ubiquitous condition. This structure approves efficient social and intellectual interaction between users in ubiquitous Learning Management System environment.Â